PENGARUH TINGKAT PROFITABILITASTERHADAP HARGA SAHAMPADA PT BANK NEGARA INDONESIA (PERSERO) TBK. - Yulia Nurhasanah,, - (2009)
This study aimed to find out the effect of profitability level on the stock price in PT Bank Negara Indonesia (Persero) Tbk. The profitability level of this study used Return on Assets as independent variable, while the stock price was dependent variable. The method used in this study is verificative method aimed at examining the truth of knowledge and testing hypothesis. The type of study was correlation study intended to determine whether there was an association among two variables or more, and how significant the correlation among the variables was. The technique of data collection used in this study was documentation a literature study, for each variable, it was quantitative. To find out the degree of independent variable correlation toward dependent variable, the writer used Product Moment Correlation Coefficient. To find out how significant the effect of profitability level on the stock price using determination coefficient. The study result showed that there was a positive, weak correlation, but there must be a profitability level with its stock price by 0.27. The significance of profitability level on the stock price was 43,31%, while the rest of 92,71% was influenced by other factors such as demand and bargaining law, interest rate, foreign currency, foreign fund in stock exchange, Combined Stock Price Index (Indeks Harga Saham Gabungan/ IHSG), rumors and etc. From the testing result, it was stated that the hypothesis was accepted.